2021
DOI: 10.1111/eva.13257
|View full text |Cite
|
Sign up to set email alerts
|

Human‐modified canids in human‐modified landscapes: The evolutionary consequences of hybridization for grey wolves and free‐ranging domestic dogs

Abstract: Introgressive hybridization between domestic animals and their wild relatives is an indirect form of human-induced evolution, altering gene pools and phenotypic traits of wild and domestic populations. Although this process is well documented in many taxa, its evolutionary consequences are poorly understood. In this study, we assess introgression patterns in admixed populations of Eurasian wolves and free-ranging domestic dogs (FRDs), identifying chromosomal regions with significantly overrepresented hybrid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 168 publications
(260 reference statements)
3
28
0
Order By: Relevance
“…Accordingly, reproductive isolation between domesticated mammals and their wild ancestors is frequently incomplete due to their recent divergence. For example, hybridization between wolves and domestic dogs results in introgression of hybridization-derived variants into gene pools of both canids [ 139 ]. In wolves, introgression of dog variants is mostly driven by drift, with only a small number of genes experiencing negative or positive selection due to this process [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, reproductive isolation between domesticated mammals and their wild ancestors is frequently incomplete due to their recent divergence. For example, hybridization between wolves and domestic dogs results in introgression of hybridization-derived variants into gene pools of both canids [ 139 ]. In wolves, introgression of dog variants is mostly driven by drift, with only a small number of genes experiencing negative or positive selection due to this process [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, hybridization between wolves and domestic dogs results in introgression of hybridization-derived variants into gene pools of both canids [ 139 ]. In wolves, introgression of dog variants is mostly driven by drift, with only a small number of genes experiencing negative or positive selection due to this process [ 139 ]. In free-ranging domestic dogs, the observed proportion of candidate genes under positive selection was larger than those under negative selection, suggesting that introgression from wolves may provide dogs with an adaptive advantage [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capturing signatures of hybridization events is critical to maintain the integrity of wild specimens in the ever‐expanding era of the Anthropocene (Ottenburghs, 2021 ). In this context, genome scans are useful to reveal signatures of human‐driven hybridization as those can identify introgression patterns among admixed populations of domesticated and wild species (Pilot et al, 2021 ). Introgression from free‐ranging domestic dogs into populations of Eurasian wolves for example has shown that the transfer of genetic material might reduce Eurasian's wolf viability by genetic swamping.…”
Section: Introductionmentioning
confidence: 99%
“…Introgression from free‐ranging domestic dogs into populations of Eurasian wolves for example has shown that the transfer of genetic material might reduce Eurasian's wolf viability by genetic swamping. This effect further impact genetic diversity that is already negatively affected by genetic drift associated with small population sizes resulting from hunting and habitat loss (Pilot et al, 2021 ). The study provides new perspective to address conservation efforts of wolf's genetic integrity; namely, it advocates the maintenance of large population sizes as an important measure of management strategies in order to avoid swamping by dog‐derived variants in wolf's genome (Pilot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation